''Petro-texts, plants, and people in the Anthropocene: the dark green''. Issue 2 (3rd April 2019) - Sullivan, Heather I.
ABSTRACT: The 'dark green' refers to the green plant-human relationships that undergird human cultures as well as the darkly petroleum-fueled industrialization, mass species extinctions, and strange new ecosystems in the Anthropocene. I consider briefly three petro-culture novels based on various 'road trips' that explicitly address both the long-term and massive, albeit oft-ignored, ecological power of plants whether in living vegetal form or in their rotted, processed form of petroleum products: Frank Herbert's Dune, portraying worm 'spice' as a stand-in for oil; Cormac McCarthy's The Road, eliminating all energy and plant life leaving only hungry humans; and Paolo Bacigalupi's cli fi novel focusing on calories and virulent plant diseases, The Windup Girl. These novels reveal the overlooked plant power, whether of mutant vegetal diseases, the inevitable death of all human and non-human animals without plants, or the sheer power of plant-based petroleum calories fueling our world in its drive into darkness.